2011
DOI: 10.1097/shk.0b013e31820b2e1c
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody Against RAGE Alters Gene Expression and is Protective in Experimental Models of Sepsis and Pneumococcal Pneumonia

Abstract: The RAGE (receptor for advanced glycation end products) is believed to play a role in sepsis by perpetuating inflammation. The interaction of RAGE with a variety of host-derived ligands that accumulate during stress and inflammation further induces the expression of RAGE. It was previously shown that a rat anti-RAGE monoclonal antibody protected mice from lethality in a cecal ligation and puncture model. We studied the effects of a humanized anti-RAGE monoclonal antibody in the murine pneumococcal pneumonia mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Our group previously investigated the role of RAGE in sepsis derived from S. pneumoniae pneumonia [14], showing increased RAGE expression in the lungs upon infection and a relatively protected phenotype of RAGE deficient ( rage -/- ) mice [14]. In accordance, independent investigations showed that anti-RAGE treatment improved outcome in invasive pneumococcal pneumonia [15]. However, RAGE inhibition may be ineffective or even harmful in other infectious diseases [13,16], suggesting that detrimental effects of RAGE might depend on the pathogen and/or level of RAGE expression in the primary infected organ.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our group previously investigated the role of RAGE in sepsis derived from S. pneumoniae pneumonia [14], showing increased RAGE expression in the lungs upon infection and a relatively protected phenotype of RAGE deficient ( rage -/- ) mice [14]. In accordance, independent investigations showed that anti-RAGE treatment improved outcome in invasive pneumococcal pneumonia [15]. However, RAGE inhibition may be ineffective or even harmful in other infectious diseases [13,16], suggesting that detrimental effects of RAGE might depend on the pathogen and/or level of RAGE expression in the primary infected organ.…”
Section: Introductionmentioning
confidence: 64%
“…Several animal studies have shown that RAGE is critically involved in the deleterious effects of acute inflammatory disorders, including sepsis [12,13,14,15,16]. Deletion of the rage gene was initially found to protect against the lethal effects of septic shock in polymicrobial sepsis, which was associated with a strongly reduced activation of NF-κB in the peritoneum and lungs [12].…”
Section: Introductionmentioning
confidence: 99%
“…RAGE is highly expressed in the lung (27) and has been shown to contribute to host defense against Klebsiella pneumoniae pneumonia but exacerbates disease in mouse models of Streptococcus pneumoniae pneumonia (16,17), suggesting that RAGE signaling impacts disease severity in a pathogen-specific manner. To advance the understanding of RAGE signaling in host defense against bacterial pneumonia, the impact of RAGE on outcomes of A. baumannii was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…RAGE has been shown to either contribute to the control of infection or enhance disease severity depending on the pathogen and infection model studied. RAGE contributed to host defense in a murine model of Klebsiella pneumoniae pneumonia, but loss of RAGE resulted in decreased mortality in a murine model of Streptococcus pneumoniae pneumonia (16)(17)(18). Similarly, RAGE Ϫ/Ϫ mice had reduced mortality in a cecal ligation and puncture model of sepsis, but the loss of RAGE did not alter disease severity in a S. pneumoniae model of sepsis (19)(20)(21).…”
mentioning
confidence: 99%
“…RAGE inhibitors (TTP4000) are now in clinical development for use in Alzheimer's patients (Transtech Pharma). Other strategies, including RAGE- IgG fusion proteins (53), anti-RAGE mAb (54), and recombinant soluble RAGE (55), have been used to inhibit RAGE signaling in preclinical models across other diseases. All of these strategies have focused on the ligand-RAGE interaction without any consideration for ligand specificity.…”
Section: Cd11bmentioning
confidence: 99%